StingReady: A Novel Device for Controlled Insect Sting Challenge—From Field Capture to Clinical Application - Xesús Feás; Margarita Armisén; Sara López-Freire; Manuela Alonso-Sampedro; Carmen Vidal (Toxins)
Reliable assessment of protection in venom immunotherapy (VIT) patients remains a clinical challenge, especially due to the limitations of conventional sting challenge tests (SCTs), which require complex insect handling and may compromise test accuracy. This study introduces StingReady, a novel, user-friendly device designed to streamline the SCT process by enabling safe, efficient, and minimally manipulative exposure to hymenopteran stings. For the first time, StingReady was applied to conduct SCTs with Vespa velutina, an invasive hornet species of increasing clinical relevance. The device was tested in a real-world setting at Belvís Park in Santiago de Compostela, Spain, where hornets were successfully captured and transported to the hospital without anesthesia or limb removal. The design features adjustable mesh sizes, allowing compatibility with various hymenopteran taxa. Using StingReady, nine patients underwent SCTs with no need for direct insect handling during the hospital procedure. The process improved patient safety and comfort while preserving the insect’s natural stinging behavior, thereby enhancing test reliability. This study demonstrates that StingReady significantly improves SCT methodology, offering a practical, reproducible, and ethically sound alternative for evaluating VIT efficacy across diverse hymenopteran species.